2001
DOI: 10.1039/b101657l
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and computational studies of the composition and structure of activated complexes in the asymmetric deprotonation of cyclohexene oxide by a norephedrine-derived chiral lithium amide†

Abstract: Rational design of efficient chiral lithium amides for enantioselective deprotonations demands understanding of the origin of the selectivity. The mechanism of deprotonation of cyclohexene oxide 1 by lithium (1R,2S )-N-methyl-1phenyl-2-pyrrolidinylpropanamide 3, which yields (S )-cyclohex-2-en-1-ol (S )-5 in 93% enantiomeric excess in tetrahydrofuran (THF ), has been investigated. Kinetics have been used to show that the reaction is first order with respect to the reagents 1 and 3, respectively. NMR investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…This made no difference to the 6 Li NMR spectrum, or to the cross-peaks observed for the mixed-metal amide in the corresponding 6 Li, 1 H -HOESY spectrum. These observations showed that the mixed-metal amide in Et 2 O must be an asymmetric dimer with methoxy coordinated to lithium, leaving sodium exposed to THF solvent coordination.…”
Section: Characterization Of Lithium Amides In Thfmentioning
confidence: 73%
See 4 more Smart Citations
“…This made no difference to the 6 Li NMR spectrum, or to the cross-peaks observed for the mixed-metal amide in the corresponding 6 Li, 1 H -HOESY spectrum. These observations showed that the mixed-metal amide in Et 2 O must be an asymmetric dimer with methoxy coordinated to lithium, leaving sodium exposed to THF solvent coordination.…”
Section: Characterization Of Lithium Amides In Thfmentioning
confidence: 73%
“…The lithium signal of the dimeric mixed-metal amide shifted continuously upfield with increasing THF concentration. With 12 equivalents of THF (per lithium) added, the 6 Li, 1 H HOESY spectrum revealed strong cross-peaks between the lithium atom of the mixed-metal amide at d = 1.1 ppm and the THF protons at d = 3.58 ppm, as well as the protons of the methoxy group of 1 at d = 3.36 ppm. In the THF-solvated mixed-metal dimer both lithium and sodium atoms were coordinated by methoxy groups, in agreement with our previous studies of chiral lithium amides derived from a-amino acids.…”
Section: Characterization Of Lithium Amides In Thfmentioning
confidence: 97%
See 3 more Smart Citations